2021
DOI: 10.1093/eurjpc/zwab181
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the HCM Risk-Kids model for predicting sudden cardiac death in childhood hypertrophic cardiomyopathy

Abstract: Aims Sudden cardiac death (SCD) is the most common mode of death in childhood hypertrophic cardiomyopathy (HCM). The newly developed HCM Risk-Kids model provides clinicians with individualized estimates of risk. The aim of this study was to externally validate the model in a large independent, multi-centre patient cohort. Methods and results A retrospective, longitudinal cohort of 421 patients diagnosed with HCM aged 1–16 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 31 publications
1
30
0
1
Order By: Relevance
“… 4 As sudden death is a rare event, a composite definition of life-threatening arrhythmias was used for this study, which includes appropriate ICD therapies. This is in keeping with previous studies in adults and children with HCM, 11 , 27 , 36 , 39 but it is plausible that not all appropriate therapies would have necessarily resulted in sudden death untreated. Genetic testing was not performed systematically in this cohort, therefore it is beyond the scope of this study to investigate the yield of genetic testing in preadolescent nonsyndromic HCM.…”
Section: Discussionsupporting
confidence: 90%
“… 4 As sudden death is a rare event, a composite definition of life-threatening arrhythmias was used for this study, which includes appropriate ICD therapies. This is in keeping with previous studies in adults and children with HCM, 11 , 27 , 36 , 39 but it is plausible that not all appropriate therapies would have necessarily resulted in sudden death untreated. Genetic testing was not performed systematically in this cohort, therefore it is beyond the scope of this study to investigate the yield of genetic testing in preadolescent nonsyndromic HCM.…”
Section: Discussionsupporting
confidence: 90%
“…A large-scale external validation study of HCM Risk-Kids was reported in 2022, confirming the ability of the model with a threshold of >6% risk at 5 years to identify over 70% of children with a major arrhythmic event and a C-statistic of 0.75. 93 Additional external validation was provided from a national cohort, in which similar performance was observed (C-statistic 0.69, sensitivity 73%, positive predictive value 22%, and negative predictive value 95%). 47 In this study, using data from ≥7 years of age in patients with a diagnosis in infancy improved the C-statistic to 0.76, and combining HCM Risk-Kids score with electrocardiogram risk score improved specificity and C-statistic compared with either measure alone.…”
Section: Hypertrophic Cardiomyopathy Risk-kidsmentioning
confidence: 80%
“…Norrish et al 109 have reported the HCM Risk-Kids risk prediction model, which is based on unexplained syncope, degree of hypertrophy, left atrial diameter, and nonsustained supraventricular tachycardia in a cohort of 421 patients 1 to 16 years of age. If all 4 risk factors were present, the 5-year risk of experiencing the composite end point was ≈10%.…”
Section: Management Of Therapy In Pediatric Patients At Risk For Deve...mentioning
confidence: 99%